(untitled) (Journal of the College of Basic Education, 2022)
With the beginning of this century, the computer use dose not limited to management, statistics .. etc. The rapid technology development of computer industry make it available and necessary in various fields. Education has an important and vital field in our life therefore many educational programs packages produced in several specialization and education levels. All previous studies proved that computer with its facilities reinforced the private skills of students for progressing their abilities when computer used for designing and building the educational programs (Packages). The technical and engineering education distinguished by its large needs to application and practice, which needs many devices and implementation tools for engineering lessons. The educational programs appear as an active tools because it is exactness in mathematics, result representation ability, attractive by dialogue, motion and colors for create an interaction between user (student) and tool (computer), and large quantity storage of data and information which can consider it as an experience save for engineers at the future. The current research focus on how to use the computer as an active technical tool in both educational techniques and individual education concepts, by computer usage methods and programming approaches for designing, and steps of educational programs preparation. In addition to demonstrate some examples from previous studies with it’s effects in rising the education level in general and especially for engineering , included the private work of researcher in Iraq. Finally, this research present the important conclusions and suggestions about the using of computer as assistant tool in education and training to habilitate the engineers, with the role of educational programs to serve and develop the community